2009
DOI: 10.1377/hlthaff.28.4.w634
|View full text |Cite
|
Sign up to set email alerts
|

Expanding The Capacity Of Nursing Education

Abstract: Assuring a nurse workforce that is large enough and possesses the right competencies for the changing demographic and health reform scenarios of the early twenty-first century is nothing short of an imperative. Getting there will involve continual recruitment of a talented and diverse group of people and increasing nurses' progression to a more highly educated workforce, no matter where they enter the profession. These actions will enable the United States to fill vacant nursing faculty positions as we simulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…3 Furthermore, nursing schools have identified shortages of clinical sites as one of the most important factors limiting the expansion of nursing programs. 4 Similar concerns apply to PA education as the number of PA programs has grown and is projected to grow steadily. As of October 2012, the number of accredited PA programs in the United States reached 170, and it is expected to reach 218 programs by 2025.…”
Section: Discussionmentioning
confidence: 97%
“…3 Furthermore, nursing schools have identified shortages of clinical sites as one of the most important factors limiting the expansion of nursing programs. 4 Similar concerns apply to PA education as the number of PA programs has grown and is projected to grow steadily. As of October 2012, the number of accredited PA programs in the United States reached 170, and it is expected to reach 218 programs by 2025.…”
Section: Discussionmentioning
confidence: 97%
“…This has resulted in qualified applicants being rejected from the nursing course, leading to a vicious cycle (Cleary et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, studies showed that there have been nursing faculty shortages due to competition from other career paths and a lack of qualified educators in training new nursing students. This has resulted in qualified applicants being rejected from the nursing course, leading to a vicious cycle (Cleary et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, there are more postsecondary institutions, including some community colleges, offering degrees in nursing which in turn raises the critical question of the form that scholarship should take in these institutions. Third, it is anticipated that the nursing shortage will be most acute in the academic sector and the problem therefore is one of how scarce human resources should be directed -for the development of the profession and the discipline (CASN, 2010;Cleary et al, 2009;Nursing Education Council of British Columbia, 2011).…”
Section: Introductionmentioning
confidence: 99%